The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1101/2022.03.11.22271527
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 reinfections during the first three major COVID-19 waves in Bulgaria

Abstract: Background: The COVID-19 pandemic has had a devastating impact on the world over the past two years (2020-2021). One of the key questions about its future trajectory is the protection from subsequent infections and disease conferred by a previous infection, as the SARS-CoV-2 virus belongs to the coronaviruses, a group of viruses the members of which are known for their ability to reinfect convalescent individuals. Bulgaria, with high rates of previous infections combined with low vaccination rates and an elde… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 169 publications
0
2
0
Order By: Relevance
“…First, a majority of the population must have been infected by that point (other-wise the IFR in Bulgaria would have to exceed 2%, which is unlikely), although how many exactly have been infected is not possible to say in the absence of an anti-nucleocapside serosurvey (and even then, seroreversion would probaly bias estimates downwards). Second, reinfections became an increasingly common phenomenon, first with the arrival of the Delta variant 38 , and especially after the appearance of Omicron. Third, the virulence of SARS-CoV-2 prior to Omicron was increasing, with the Alpha variant being more severe than the WT and the Delta variant being even more severe than Alpha; meanwhile the IFR estimates from 2020 and early 2021 were based on the WT virus.…”
Section: Discussionmentioning
confidence: 99%
“…First, a majority of the population must have been infected by that point (other-wise the IFR in Bulgaria would have to exceed 2%, which is unlikely), although how many exactly have been infected is not possible to say in the absence of an anti-nucleocapside serosurvey (and even then, seroreversion would probaly bias estimates downwards). Second, reinfections became an increasingly common phenomenon, first with the arrival of the Delta variant 38 , and especially after the appearance of Omicron. Third, the virulence of SARS-CoV-2 prior to Omicron was increasing, with the Alpha variant being more severe than the WT and the Delta variant being even more severe than Alpha; meanwhile the IFR estimates from 2020 and early 2021 were based on the WT virus.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 One study found that the reduced risk of hospitalization following reinfection persisted when disaggregated by age. 17 No study has clearly disaggregated by severity of hospitalization, such as considering the distinction between an emergency department (ED) visit, an inpatient hospitalization, and an inpatient hospitalization requiring intensive care. In this work, we aim to assess the association between the severity of initial infection and severity of first reinfection to contribute more granular findings disaggregated by severity of hospitalization.…”
Section: Introductionmentioning
confidence: 99%